Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Memilih Produk Tabungan BritAma Bank BRI Di Kelurahan Fatukoa Kota Kupang - Darius Lado Miha; Petrus E. De Rosari; Novi T. Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The main problem in this research is what factors influence customer decisions in choosing BRI Bank Britama Savings Products in Fatukoa Village. The aim of this research is to see and explain what influences the decisions of Fatukoa Village customers in saving with Britama Savings Products. This type of research uses descriptive qualitative research. The data sources in this research are primary data and secondary data. Where data collection uses interview, observation, and documentation techniques. determining informants using Purposive Sampling, totaling 6 people. The time and place of the research was carried out in the 2023-2024 academic year, on a number of customers who live in Fatukoa Village, Kupang City. The results of this research explain that the factors that influence customers' decisions in choosing Britama Bank BRI savings products are influenced by cultural factors because cultural influences play a key role in customer decisions. The socialization process from the experience of being a customer for eight years, the use of banking products since the beginning of college, and the management of business transactions are the main factors in choosing Britama Savings. Social Factors due to the existence of reference groups, both from friends and family, have a big impact. Suggestions from friends about the benefits of interest rates and easy access to BRI Bank's online services, as well as recommendations from wives who are BRI Bank customers, are taken into consideration in the decision to save on Britama Products. Personal Factors due to Age, life cycle stage, work and economic environment are factors personal influences on product choices. The decision to save in BRI Bank Britama Products is based on long-term goals, investment, financial discipline, and economic considerations as well as income that can be invested, and Psychological Factors because the motivation for opening a Britama Savings account is related to biogenic and psychogenic needs, such as increasing pension funds, long-term investment, increasing financial discipline, and building savings habits. Trust and positive attitudes towards Britama products, supported by the reputation and security of BRI Bank, also play a key role in decision making. Apart from that, information from reference groups, socialization experiences, economic considerations, and trust in banking institutions are key factors that shape customer decision behavior.